(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The aim of this study is to examine the unsteady two-dimensional flow of an electrically conducting, viscous, and incompressible fluid over a stretching surface in the presence of a constant transverse magnetic field. Through the use of a similarity transformation, the original boundary layer equations governing the problem are transformed into nonlinear ordinary differential equations. These equations are then numerically solved using the fourth-order Runge-Kutta method coupled with a shooting technique. The study explores the influence of various parameters on both the velocity and temperature distributions, along with the skin-friction coefficient and Nusselt number.